2018
DOI: 10.1519/jsc.0000000000002038
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity of the Sympatho-Adrenomedullary System Without Any Modification of the Hypothalamic-Pituitary-Adrenal Axis After Food Restriction Among High-Level Weightlifters

Abstract: Durguerian, A, Filaire, E, Drogou, C, Sauvet, F, Bougard, C, and Chennaoui, M. Hyperactivity of the sympatho-adrenomedullary system without any modification of the hypothalamic-pituitary-adrenal axis after food restriction among high-level weightlifters. J Strength Cond Res 32(6): 1643-1655, 2018-We examined the effects of 6 days of food restriction on salivary α-amylase (sAA), cortisol and dehydroepiandrostenedione (DHEA) awakening responses, psychological parameters and performance among 11 international wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Chromogranin-A (CgA) is released along with catecholamines from the adrenal medulla and the sympathetic nerve endings (O'Connor et al 1984), and is perceived as a stress marker, notably a driving-induced psychological marker (Yamakoshi et al 2009). Recently, we confirmed that both HPA axis and SAM work mediate the physiological response to perceived stressor (Durguerian et al 2018a(Durguerian et al , 2018b. Although the dissociation of both axes has been associated to stressful situations (Ali and Pruessner 2012), an opposite regulation between both stress systems should be perceived as a potential compensating mechanism (Chennaoui et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Chromogranin-A (CgA) is released along with catecholamines from the adrenal medulla and the sympathetic nerve endings (O'Connor et al 1984), and is perceived as a stress marker, notably a driving-induced psychological marker (Yamakoshi et al 2009). Recently, we confirmed that both HPA axis and SAM work mediate the physiological response to perceived stressor (Durguerian et al 2018a(Durguerian et al , 2018b. Although the dissociation of both axes has been associated to stressful situations (Ali and Pruessner 2012), an opposite regulation between both stress systems should be perceived as a potential compensating mechanism (Chennaoui et al 2016).…”
Section: Introductionmentioning
confidence: 83%
“…Other researchers pointed out how overly obsessive regulatory behaviors may lead to stress-response activation. Durguerian et al showed that when athletes restricted food intake, the bodily stress response was activated asymmetrically [ 127 ]. This suggested that obsessively controlling food intake could lead to adverse psychological and physiological bodily changes.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…Among various aspects of the diurnal cycle that has been studied to investigate potential dysfunction in the HPA axis is the cortisol awakening response (CAR), which represents a sharp increase in cortisol levels over the first 30-45 min following morning awakening [12], knowing that CAR is a distinct feature of the diurnal cycle [13]. It has been introduced as a measure of the HPA axis reactivity to awakening stress, possibly reflecting modifications in the HPA axis activity after stressors [14,15]. Area under the curve (AUC) is another measure to assess the overall secretion of homones over a specific time period [16].…”
Section: Introductionmentioning
confidence: 99%